2019
DOI: 10.1590/1413-785220192701189400
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Implant Density in the Management of Lenke 1b and 1c Adolescent Idiopathic Scoliosis

Abstract: Objective:To compare radiographic and surgical outcomes of Lenke 1B and 1C patterns.Methods:One hundred twenty patients with Lenke 1B and 1C scoliosis were grouped according to implant density as follows: low density (LD) of ≤1.4 and high density (HD) of >1.4. Matched subgroups (30 patients each) based on age, curve magnitude, and body mass index (BMI) were analyzed. Radiographic parameters were evaluated before operation, immediately after operation (ipo), and at 2 years’ follow-up. SRS-30 was administered be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Similar results were reported by Garcia et al (10) who included 79 patients and there was a statistically significant difference in the postoperative Cobb angle as compared to the preoperative Cobb angle (7° vs 53°) respectively. The results of the current study also agree with Kilinc et al (11) who showed that the preoperative mean main thoracic Cobb angle measured 61.2° and corrected to 25.3° postoperatively, and was 28.5° at 2-year follow-up.…”
Section: Radiological Outcomessupporting
confidence: 92%
“…Similar results were reported by Garcia et al (10) who included 79 patients and there was a statistically significant difference in the postoperative Cobb angle as compared to the preoperative Cobb angle (7° vs 53°) respectively. The results of the current study also agree with Kilinc et al (11) who showed that the preoperative mean main thoracic Cobb angle measured 61.2° and corrected to 25.3° postoperatively, and was 28.5° at 2-year follow-up.…”
Section: Radiological Outcomessupporting
confidence: 92%
“…Some authors reported that, in patients with high implant density, a significantly better correction rate could be achieved; however, there was no difference in the postoperative coronal balance and trunk shift. 33 In contrast, Shen et al, in a retrospective study of 62 adolescent idiopathic scoliosis (AIS) patients who underwent PSF, found that there was no significant difference in the correction rate of the main thoracic curve between the low and high implant density groups. 34 The involvement of two attending surgeons distinguishes the current study from previous reports.…”
Section: Discussionmentioning
confidence: 98%
“…Previous authors have reported that higher implant density increased surgical time. Kilinc et al, 23 in his review of 120 patients, reported that the high-density group ( > 1.4 screws per level) had significantly longer surgical time (293.6 ± 73.1 min) compared with the low-density group (251.0 ± 68.1 min) (P < 0.001). Shen et al 24 reported a shorter operation duration in the low-density group (278.4 vs. 331.0 min, P = 0.004).…”
Section: Discussionmentioning
confidence: 99%